A Two‐Generation Education Intervention and Children's Attendance in Head Start. Issue 6 (8th August 2020) - Sommer, Teresa Eckrich; Schneider, William; Chor, Elise; Sabol, Terri J.; Chase‐Lansdale, P. Lindsay; Brooks‐Gunn, Jeanne; Yoshikawa, Hirokazu; Morris, Amanda; King, Christopher
Abstract : Two‐generation human capital programs seek to promote the education of parents and children simultaneously. This study examines relations between family participation in Career Advance, which recruits parents of Head Start children into a workforce training program, and children's Head Start attendance. The sample included 293 children (on average 4 years old) and their parents. After one semester, Career Advance children demonstrated higher rates of attendance and lower rates of absence and chronic absence (missing 10% or more of school days) than matched comparison children. These associations were similar across a range of high‐ and low‐risk subgroups at baseline. These findings are discussed in terms of the implications of a family systems approach for improving children's Head Start attendance.